Exploring and modelling the effects of agricultural land management and climate change on agroecosystem services in the Eastern Cape, South Africa - Choruma, Dennis Junior (Rhodes University, Faculty of Science, Institute for Water Research, 2020)
The aims of this study were to evaluate the impacts of agricultural land management strategies and climate change on irrigated maize production in the Eastern Cape, South Africa. To achieve these aims, the study was guided by two overarching research questions, subsequently broken down into more specific questions. The first research question examined the reasons behind farmers' current agricultural land management practices, the values they assigned to different agroecosystem services, their perceptions of climate change and the adaptation strategies they used to address challenges associated with agricultural crop production and climate change. To answer these questions, a survey of conventional farmers in the Eastern Cape was carried out. The survey targeted farmers who used fertilisers and irrigation water in their day to day farming. Results showed that farmers recognised the different benefits that agroecosystems provided even though they were not familiar with the term 'ecosystem services.' Farmers assigned a high value to food provisioning compared to other agroecosystem services and managed their farms for maximum crop yields or maximum crop quality. Fertiliser and irrigation water management decisions were based on multiple factors such as cost, availability of farming equipment and crop yield or crop quality considerations. Survey results showed that while most farmers were able to state the amount of fertiliser used per growing season, the majority of farmers did not know the amount of water they used per growing season. From the farmers' survey it was recommended that extension services and agricultural education programmes be strengthened in the region to increase farmers' knowledge on effective agricultural land management strategies that support sustainable intensification. The second research question investigated the effects of agricultural land management strategies and climate change on crop yields in the Eastern Cape. This investigation was done in three steps. First, a crop model, the Environmental Policy Integrated Climate (EPIC) model was calibrated and validated using limited field data from maize variety trials carried out at the Cradock Research Farm in the Eastern Cape. Calibration and validation results proved satisfactory with model efficiencies (Nash Sutcliffe, NSE) greater than 0.5 for both calibration and validation. It was concluded that limited data from field trials on maize that only included grain yield and agricultural land management dates can be used for the calibration of the EPIC model to simulate maize production under South African conditions. In the second step, the calibrated model was applied to simulate different irrigation and fertiliser management strategies for maize production in the Eastern Cape. Different irrigation and Nitrogen (N) fertiliser levels were compared to find optimal irrigation and N fertiliser management strategies that would increase maize yields while minimising environmental pollution (nitrate leaching). Model outputs were also compared to the average yields obtained in the field trials (baseline) and to maize yields reported by farmers in the farmers' survey. Results showed that improved management of irrigation water and N fertiliser could improve farmers' maize yields from approximately 7.2 t ha-1 to approximately 12.2 t ha-1, an increase of approximately 69%. Results also revealed a trade-off between food provision and nitrate leaching. Simulations showed that increasing N fertiliser application under sufficient irrigation water levels would increase maize yields, however, this would be accompanied by an increase in N leaching. Lastly, the EPIC model was then applied to simulate the effects of future climate change on irrigated maize production in the Eastern Cape. For these simulations, the model was driven by statistically downscaled climate data derived from three General Circulation Models (GCMs) for two future climate periods, (2040-2069) and (2070-2099), under two Representative Concentration Pathways (RCPs): RCP 4.5 and RCP 8.5. Future maize yields were compared to the baseline (1980-2010) maize yield average. All three climate models predicted a decline in maize yields, with yields declining by as much as 23.8% in RCP 8.5, 2070-2099. Simulations also predicted increases in average daily maximum and minimum temperatures for both the two future climate periods under both RCPs. Results also indicated a decrease in seasonal irrigation water requirements. Nitrate leaching was projected to significantly increase towards the end of the century, increasing by as much as 373.8% in RCP 8.5 2070-2099. Concerning farmers' perceptions of climate change, results showed that farmers were aware of climate change and identified temperature and rainfall changes as the most important changes in climate that they had observed. To adapt to climate change, farmers used a variety of adaptation strategies such as crop rotations and intercropping. Apart from challenges posed by climate change, farmers also faced other challenges such as access to markets and access to financial credit lines, challenges that prevented them from effectively adapting to climate change. The study therefore recommended that appropriate and adequate strategies be designed to help farmers in the region offset the projected decrease in maize production and increase crop yields while minimising negative environmental impacts.
Keywords: Agricultural ecology -- South Africa -- Eastern Cape; Agriculture -- Environmental aspects -- South Africa -- Eastern Cape; Crops and climate -- South Africa -- Eastern Cape; Corn -- Climatic factors -- South Africa -- Eastern Cape; Land use -- South Africa -- Eastern Cape